Emicizumab prophylaxis: Prospective longitudinal real‐world follow‐up and monitoring. Issue 3 (23rd April 2021) - Barg, Assaf A.; Budnik, Ivan; Avishai, Einat; Brutman‐Barazani, Tami; Bashari, Dalia; Misgav, Mudi; Lubetsky, Aaron; Kuperman, Amir A.; Livnat, Tami; Kenet, Gili
Abstract: Introduction: Real‐world data on prophylaxis of severe haemophilia A (HA) patients treated by emicizumab are scarce. Aim: To study the efficacy and safety of longitudinal emicizumab prophylaxis and assess laboratory monitoring correlations in a large patient cohort. Methods: HA patients with and without FVIII inhibitors, initiating emicizumab prophylaxis, were prospectively enrolled. Bleeding, adverse events and surgeries were documented. FVIII inhibitors, emicizumab levels and thrombin generation (TG) were sequentially measured. Results: A total of 107 patients, including 58 children (whose median (IQR) age was 6 (1–11) years) with severe HA, composed the study cohort. Twenty‐nine per cent (31/107) of our HA patients had FVIII inhibitors. Patients were followed for a median of 67 weeks (up to 144 weeks). Fifty‐three patients, whose median follow‐up was 53 weeks, experienced zero bleeds. Most bleeds (94%) among children were trauma‐related, whereas 61% of adults sustained spontaneous joint bleeds. Four patients experienced major bleeds, with a fatal outcome in one infant, who also presented with central venous line thrombosis. No other serious adverse events were encountered. Seven patients have decided to stop emicizumab treatment for various reasons. Emicizumab plasma levels increased after emicizumab prophylaxis initiation, and values were maintained during follow‐up, in all but one patient, suspected of anti‐drug antibodies. A significant reduction of FVIII inhibitor levels was noted among inhibitor patients. TG was increased and sustained yet could not prognosticate bleeding risk. Conclusion: Emicizumab prophylaxis was mostly well tolerated, although 50% of patients experienced breakthrough bleeds. Routine TG monitoring is not obligatory, and further studies are warranted in selected patient populations.